Biliary strictures: endoscopic assessment and management. Issue 2 (10th February 2017) - Paranandi, Bharat; Oppong, Kofi W
Abstract : The diagnosis of biliary strictures can be challenging. Endoscopy has an established role in the diagnosis and therapy of biliary strictures. However, the diagnostic yield from conventional endoscopic retrograde cholangiopancreatography tissue sampling is modest. Improvements in existing technologies as well as the implementation of novel technologies and techniques have the potential to improve the diagnostic performance of endoscopy and expand its therapeutic role. Recent studies have enabled greater clarity about the role of preoperative biliary drainage and the choice of stents in this setting as well as the utility of metal stents in benign and malignant disease.